A survey of statistical design and linear models - Srivastava, Jagdish N.; Srivastava, Jagdish Narain, 1933-. (Amsterdam : North-Holland Pub. Co. ; New York American Elsevier, 1975)
Invited papers and abstracts of contributed papers presented at the international symposium on statistical design and linear models, Colorado State University, Fort Collins, March 19-23, 1973.
Includes bibliographies and index.
Keywords: Experimental design -- Congresses; Linear models (Statistics) -- Congresses; Linear Models